AI and the Future of War: The Impact of Machine Learning in Security Practice - Li, Lingjuan (International Journal of Computer Science and Information Technology, 2024)
This paper explores the relationship between artificial intelligence (AI) and future wars, and focuses on how machine learning strengthens safety practice. Based on Wu Qianze's paper in National Defense Science, Technology and Industry, Issue 5,2019, this paper expounds the wide application of AI in the military field and the great potential of machine learning in improving security protection. Through a review of existing studies, this paper presents a series of recommendations to enhance safety practices designed to provide guidance for future research and applications.